Consumer Preferences and Influencing Factors for Purchase Places of Organic Food Products: Empirical Evidence from South India - Nandi, Ravi; Bokelmann, Wolfgang; Gowdru, Nithya Vishwanath; Dias, Gustavo (Indian Journal of Marketing, 2014)
The market for organic products in India is in its infancy, and knowledge about organic consumers in the country is definitely under-researched. The objective of this paper is to gain knowledge about consumers’ preferences regarding the purchase places of organic products in Bangalore, the capital of Karnataka state, India. The consumers’ preferred places of purchase and their socio - demographic characteristics were collected by means of face to face interviews with 201 consumers by using the stratified simple random sampling technique at different locations in Bangalore. The data obtained from the survey were analyzed with descriptive statistics, Friedmen’s test, Kendall’s W test, and seemingly unrelated regression. The results revealed that the most preferred purchase places for organic food products were specialized organic stores and supermarkets. The least preferred purchase places were the local open markets and conventional retail shops. Furthermore, the results from seemingly unrelated regression showed that the preferences about places to purchase organic food products were mainly influenced by gender, education, family size, and family income. Policy makers in agricultural marketing, institutions who are involved in organic food marketing, and producers should consider the differences in consumer preferences and their socio-demographic attributes for determining and supporting efficient marketing channels for organic food products.